2019
DOI: 10.20892/j.issn.2095-3941.2018.0410
|View full text |Cite
|
Sign up to set email alerts
|

CSN6 promotes tumorigenesis of gastric cancer by ubiquitin-independent proteasomal degradation of p16INK4a

Abstract: Objective: CSN6 is a vital subunit of the constitutive photomorphogenesis 9 (COP9) signalosome (CSN), which is responsible for development disorders and promotes ubiquitin-26S proteasome-dependent degradation in vitro and vivo. Its role in the tumor development of gastric cancer remains unclear. In this study, we investigated the role of CSN6 in gastric cancer progression. Methods: Human gastric cancer samples were collected and immunohistochemistry was performed to identify the role of CSN6 in gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Thus, aberrant expression of COPS subunits may contribute to cancer development and progression. Indeed, COPS subunit overexpression has been detected in breast cancer [ 40 42 ], HCC [ 18 , 43 ], colorectal cancer [ 44 ], gastric cancer [ 23 , 45 ], pancreatic cancer [ 46 , 47 ], myeloma [ 48 ], non-small cell lung cancer [ 49 ], prostate cancer [ 50 ], and osteosarcoma [ 51 ]. Overexpression of COPS5 has also been implicated in lymph node metastasis [ 52 ] and histological tumor progression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aberrant expression of COPS subunits may contribute to cancer development and progression. Indeed, COPS subunit overexpression has been detected in breast cancer [ 40 42 ], HCC [ 18 , 43 ], colorectal cancer [ 44 ], gastric cancer [ 23 , 45 ], pancreatic cancer [ 46 , 47 ], myeloma [ 48 ], non-small cell lung cancer [ 49 ], prostate cancer [ 50 ], and osteosarcoma [ 51 ]. Overexpression of COPS5 has also been implicated in lymph node metastasis [ 52 ] and histological tumor progression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSN6 gene copy number is positively correlated with tumor size 90 . Correspondingly, high CSN6 expression is significantly correlated with TNM stage, depth of invasion-pT status and lymph node metastasis-pN status in gastric cancer, breast cancer, and pancreatic adenocarcinoma 80,84,86 . Kaplan-Meier analysis has indicated that higher CSN6 expression is associated with shorter overall survival in patients with pancreatic cancer, HCC, or CRC 82,83,85 .…”
Section: Csn6 Overexpression In Cancermentioning
confidence: 93%
“…CSN6 is overexpressed in many types of cancer, according to analysis of human cancer patient data sets from Gene Expression Omnibus and Oncomine 79 . Furthermore, studies increasingly demonstrate that CSN6 expression is enhanced in various human cancers, including breast cancer 80,81 , HCC 82 , CRC 83 , gastric cancer 84 , pancreatic cancer 85,86 , melanoma 87 , glioblastoma 88 , and oral squamous cell carcinoma 89 . These studies have indicated that CSN6 is associated with the occurrence and development of carcinogenesis.…”
Section: Csn6 Overexpression In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…p16 , a cyclin-dependent kinase inhibitor, arrests cells in the G1 phase. Numerous carcinogens, including miR-30 and constitutive photomorphogenesis 9 signalosome 6, cause cancer by suppressing p16 expression, enhancing cell division, and interfering with efficient cellular senescence [ 197 , 198 ]. Liu et al also demonstrated that ablation of p16 in B cells could reverse aging while significantly increasing the incidence of B-cell neoplasms [ 199 ].…”
Section: The Deepest Connection: Genetics Of Aging and Cancersmentioning
confidence: 99%